Tuning the orientation of few-layer MoS2 films using one-zone sulfurization. Issue 51 (19th September 2019) - Sojková, Michaela; Vegso, Karol; Mrkyvkova, Nada; Hagara, Jakub; Hutár, Peter; Rosová, Alica; Čaplovičová, Mária; Ludacka, Ursula; Skákalová, Viera; Majková, Eva; Siffalovic, Peter; Hulman, Martin
Abstract : Schematic representation of the GIWAXS measurements on HA and VA MoS2 layers. Abstract : Few-layer MoS2 films are promising candidates for applications in numerous areas, such as photovoltaics, photocatalysis, nanotribology, lithium batteries, hydro-desulfurization catalysis and dry lubricants, especially due to their distinctive electronic, optical, and catalytic properties. In general, two alignments of MoS2 layers are possible – the horizontal and the vertical one, having different physicochemical properties. Layers of both orientations are conventionally fabricated by a sulfurization of pre-deposited Mo films. So far, the Mo thickness was considered as a critical parameter influencing the final orientation of MoS2 layers with horizontally and vertically aligned MoS2 grown from thin (1 nm) and thick (3 nm) Mo films, respectively. Here, we present a fabrication protocol enabling the growth of horizontally or vertically aligned few-layer MoS2 films utilizing the same Mo thickness of 3 nm. We show that the sulfur vapor is another parameter influencing the growth mechanism, where a sulfurization with higher sulfur vapor pressure leads to vertical MoS2 layers and slow sulfur evaporation results in horizontally aligned layers for a thicker Mo starting layer.